Platelets in Tumor Progression: A Host Factor That Offers Multiple Potential Targets in the Treatment of Cancer. Issue 8 (August 2014) - Sharma, Deva; Brummel‐Ziedins, Kathleen E.; Bouchard, Beth A.; Holmes, Chris E.
<x xml:space="preserve">Abstract</x> While platelets are well known to play a central role in hemostasis and thrombosis, there is emerging experimental evidence to suggest that they also mediate tumor cell growth, dissemination, and angiogenesis. An increase in platelet number (thrombocytosis) and activity is seen in patients with a wide spectrum of malignancies, and the former is correlated with a decrease in overall survival and poorer prognosis. Preclinical data suggest that circulating tumor cell partnerships with platelets in the blood facilitate tumor metastases through direct interactions and secreted bioactive proteins. Platelets form aggregates with tumor cells, thereby protecting them from host immune surveillance through physical shielding and induction of "platelet mimicry." There is also laboratory evidence to suggest that activated platelets interact with cancer cells within the tumor microenvironment through paracrine signaling and direct contact, thereby promoting tumor cell growth and survival. For example, platelets release mediators of both tumor angiogenesis and osteoclast resorption. The interplay between platelets and tumor cells is complex and bidirectional with involvement of multiple other components within the tumor microenvironment, including immune cells, endothelial cells, and the extracellular matrix. We review the role of platelets in tumor progression, emphasizing the opportunity these interactions afford to target platelets and platelet function to improve patient outcomes in the cancer prevention and treatment setting. J. Cell. Physiol. 229: 1005–1015, 2014. © 2013 Wiley Periodicals, Inc.